Micro credit and rural poverty alleviation in emerging economy: the role of entrepreneurship - Md Al-Amin Mollah; Tze, Cheng Chew; Tarun Kanti Bose (Inderscience Enterprises Ltd., 2023)
Rural poverty alleviation in emerging economies (EE) poses a significant challenge due to the prevailing economic and social conditions in these regions. Microcredit programs have been widely used as a mechanism to address both social and economic issues in these contexts. Entrepreneurship is closely associated with poverty alleviation and has potential impacts on the social and economic aspects of rural areas in EE countries. This study aims to evaluate the role of entrepreneurship as both a contributing factor and a moderator. Quantitative investigations and survey data were used to test hypotheses. Our findings indicate that entrepreneurship plays a significant mediating role but insignificant moderating roles in the relationship between microcredit and poverty alleviation. This study provides theoretical and practical implications based on these results.